Novel Design of High-Gain Planar Dipole-Array Antenna for RFID 2.45 GHz. (29th January 2014) - Xie, Danpeng; Liu, Xueguan; Guo, Huiping; Yang, Xinmi
Abstract : This paper presents a novel high-gain planar dipole-array antenna for 2.45 GHz which consists of four planar dipole elements placed in two parallel lines. Phase retardation of each element is set by feeding network to form controllable radiation direction. The radiation pattern of the array is discussed according to Arrays Theorem. The measured −10 dB band is from 2.3 GHz to 2.57 GHz, and peak gain in this band is 7.5 dBi. The gain can even reach 10.5 dBi after installing additional ground. The proposed antenna has advantages of high gain, controllable direction, and planarity which are suitable for 2.45 GHz RFID base station.